2017
DOI: 10.1111/maps.12917
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally enhanced magnetization at the center of the Haughton impact structure?

Abstract: Haughton is a ~24 Myr old midsize (apparent diameter 23 km) complex impact structure located on Devon Island in Nunavut, Canada. The center of the structure shows a negative gravity anomaly of −12 mGal coupled to a localized positive magnetic field anomaly of ~900 nT. A field expedition in 2013 led to the acquisition of new ground magnetic field mapping and electrical resistivity data sets, as well as the first subsurface drill cores down to 13 m depth at the top of the magnetic field anomaly. Petrography, roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The latter has been shown to increase the NRM within impact melt rocks of the central uplift at the nearby Haughton impact structure (Zylberman et al. ). Another possibility would be a concentration of mafic, pre‐impact magmatic rocks at local scale, possibly remagnetized by the impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been shown to increase the NRM within impact melt rocks of the central uplift at the nearby Haughton impact structure (Zylberman et al. ). Another possibility would be a concentration of mafic, pre‐impact magmatic rocks at local scale, possibly remagnetized by the impact.…”
Section: Discussionmentioning
confidence: 99%
“…Ground surveys allow acquiring high‐resolution gravimetric and magnetic data over impact structures in remote areas and also enable sampling to be conducted for further laboratory analyses, to update the geological mapping and to identify possible local geophysical anomalies (e.g., the Haughton crater center; Zylberman et al. ). All these data will serve as constraints for modeling the geological (and possibly multiple) sources of the observed gravimetric and magnetic anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…*The average impact is computed from sites TUN07, 20, 21, 29, 31, 33, 36 (see text). for post-tilting remagnetization of these sedimentary rocks are thermal magnetization during cooling from impact-related heating, shock magnetization during pressure release immediately after passage of the impact shock wave, or chemical magnetization resulting from postimpact hydrothermal activity (e.g., Zylberman et al 2017). Shock remanent magnetization is excluded as the source of the impact-related magnetization because the release of the shock wave occurs before tilting, so that a shock remanence would pass a tilt test.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, by Osinski and Ferri ere (2016), of the HIS shatter cones demonstrated that their distribution is an indicator of the extent of the apparent crater diameter and obliquity of the impact, and that they play a role in reducing the strength of target rocks, thus enhancing crater collapse. Further studies of the HIS investigated the central positive magnetic anomaly (~900 nT), and concluded that impact-generated hydrothermal alteration crystallized magnetite in the uplifted basement rock, which was subsequently concentrated in the near surface, producing the very strong anomaly observed presently (Quesnel et al 2013;Zylberman et al 2017).…”
Section: History Of Haughton Investigationsmentioning
confidence: 99%